An Integrative Model of Relationship Quality in Higher Education Setting: Evidence from Serbia - Rajić, Tamara; Nikolić, Ivan; Milošević, Isidora (Industrija, 2019)
The objective of this study is to examine the formation of relationship quality and its consequences in higher education setting. The study draws on extant literature in service businesses and proposes teachers’ customer orientation as an antecedent to relationship quality, encompassing trust and satisfaction, and relationship continuity and word-of-mouth (WOM) communication as consequences of students’ perceptions of relationship quality. Structural equation modelling was applied to analyse survey data collected on a convenience sample of 236 students attending a small public faculty in Serbia. The results show that trust and satisfaction mediate the impact of teachers’ customer orientation on relationship continuity and WOM. Both trust and satisfaction emerged as direct positive determinants of WOM, whereas the impact of trust on relationship continuity is mediated via student satisfaction. Implications and limitations of the study are discussed and future research directions are provided.
Keywords: Higher education; Word-of-mouth; Relationship continuity; Trust; Satisfaction; Relationship quality; Customer orientation; Customers